Integrated Dairy Goat and Stingless Bee Farming Based on Dual-Purpose Forage Plants to Strengthen Household Food Security in a Women Farmers Group - Ratni, Eli; Lendrawati; Setyaka, Virtuous (Warta Pengabdian Andalas, 2026)
This community engagement program aimed to strengthen household food security and improve the technical capacity of the Nuhairun Women Farmers Group (WFG), locally known as Kelompok Wanita Tani (KWT) Nuhairun, in Patalangan Village, West Sumatra, through integrated dairy goat and stingless bee farming based on dual-purpose forage plants. The group consisted of 10 active female members who had prior experience in small-scale livestock and stingless bee cultivation, but their management practices remained traditional and less productive. The program focused on improving dairy goat management, stingless bee colony maintenance, hygienic honey harvesting, and the cultivation of dual-purpose forage plants, particularly Calliandra calothyrsus and Clitoria ternatea, which function as both goat feed and nectar sources for the bees. Infrastructure support included improved goat housing, additional hives, and forage planting. Training on farm management and the Business Model Canvas (BMC) was also provided to support product development and household agribusinesses. The program improved members’ technical skills, enhanced production consistency, and improved access to nutritious food at the household level. This integrated farming model has strong potential to support sustainable rural food systems and strengthen women’s participation in community-based agribusinesses.